Learning priors for Bayesian perception in normal and atypical development - McKeown, Lucy (2024)
Over recent years, biases of sensory magnitude estimations, such as central tendency bias have been thought to reveal the weighting of a Bayesian prior as estimations drifted towards the mean of the stimulus distribution.